المباني الجاهزة بين الكفاءة الإنشائية والاستدامة البيئية (Comprehensive Journal of Science, 2025)
This research aims to study prefabricated buildings and their role in achieving environmental sustainability in civil engineering, through an analysis of the concept, advantages, and challenges associated with implementing this type of construction in the Libyan context. The importance of this research stems from the urgent need to adopt modern urban solutions that align with the requirements of sustainable development and respond to the environmental and economic crises facing the traditional construction sector in Libya.The study adopted a descriptive-analytical approach, being a theoretical research project focusing on analyzing literature and previous studies related to prefabricated buildings and sustainability concepts in architecture. The research comprised three main chapters:The first chapter addressed the conceptual framework and previous studies, presenting the concepts of prefabricated construction, environmental sustainability, and prominent international models in this field. The second chapter focused on the current state of prefabricated building implementation in Libya, highlighting its key advantages, challenges, and obstacles. The third chapter explored the prospects for developing prefabricated construction within the context of sustainable development, emphasizing the importance of industrial and legislative infrastructure and community awareness in ensuring the success of this transition.The research concluded that prefabricated buildings represent a promising solution for achieving environmental and urban sustainability in Libya, provided that a comprehensive national vision is developed that relies on local manufacturing and integrates efforts between the state, the private sector, and academic institutions. It also recommended integrating sustainability concepts into engineering education and adopting clear environmental standards in the design and implementation of future housing projects.
Keywords: Prefabricated buildings, environmental sustainability, civil engineering, sustainable development, industrial construction, Libya.